A comparison of well-peer mentored and non-peer mentored athletes` perceptions of satisfaction - Hoffmann, M. D.; Loughead, T. M. (Journal of Sports Sciences, 2016)
The purpose of the present study was to compare well-peer mentored and non-peer mentored athletes` perceptions of satisfaction. A total of 444 intercollegiate athletes (272 well-peer mentored and 172 non-peer mentored) from a variety of sport teams participated in the study. Athletes from both well-peer mentored and non-peer mentored groups reported their satisfaction levels using the Athlete Satisfaction Questionnaire. The results of a MANOVA and follow-up post hoc ANOVAs showed that well-peer mentored athletes were significantly more satisfied than their non-peer mentored counterparts in terms of individual performance, personal dedication, team task contribution, team social contribution, team integration, ethics, ability utilisation and training and instruction. Overall, the findings suggest that athletes who are well-peer mentored by a teammate perceive higher satisfaction levels with various aspects of their athletic experience than athletes who are not peer mentored by a teammate. Given these positive findings, practitioners (i.e., coaches, sport psychology consultants) should inform athletes on the benefits of peer-to-peer mentoring. The practical implications of the results and strategies to promote peer athlete mentoring relationships in sport are highlighted.